The potential of switching modes of transportation analysis in a middle city region with Binary Logistic Regression Method - Basalim, Said; Akhmadali, . (Aceh International Journal of Science and Technology, 2024)
This study aimed to investigate the various factors that affect the selection of public transport in Pontianak City, West Kalimantan, including gender, age, job nature, transport ownership, travel purpose, vehicle used, and vehicle preference among the respondents. The primary data for this study was gathered through household interviews conducted in 6 sub-districts of Pontianak City. Following the process of data reduction, a total of 654 respondents' answers were available for analysis. This study employs the binomial logistic regression method to establish the connection between independent variables and binary responses, utilizing the JASP software. Comparative analysis is commonly employed in the early stages of data examination to assess the relationship between a variable and vehicle preference. The cross-tab analysis reveals a noteworthy correlation between transportation preferences and factors such as gender and age. After conducting an analysis using the binary logistic regression model method, it was found that factors such as household size, transport ownership, age, and personal status had a significant impact (p0.05). The highest odds ratio value (1.538) is associated with household size, indicating that an increase of 1 unit in household size will positively influence the likelihood of selecting a public transport mode by 1.538 times.